Peningkatan Kemampuan Menganalisis Nilai Keteladanan Teks Biografi Dengan Model Cooperative Script Kelas X SMK Swasta Kristen BNKP Gunungsitoli - Cerah Liberina Gulo; Noveri Amal Jaya Harefa (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to improve the ability to analyze the exemplary value of biographical texts for grade X students of SMK Swasta Kriten BNKP Gunungsitoli to improve learning conditions in analyzing the exemplary value of biographical texts by applying the Cooperative Script learning model. This type of research is Classroom Action Research (PTK) using the Cooperative Script learning model. In this study in the form of student written test results / assessment sheets, observation results, field notes, and documentation in learning. The research procedure is carried out in two cycles consisting of four elements of implementation 1) planning, 2) action, 3) observation, 4) reflection. The subjects of this study were grade X students of SMK Swasta Kriten BNKP Gunungsitoli even semester, totaling 15 people. The results showed an increase in ability in learning. Based on the results of the study, it was concluded that the application of the Cooperative Script learning model can improve students' ability to analyze the exemplary value of biographical texts in Class X-UPW SMK Private Christian BNKP Gunungsitoli